2005
DOI: 10.1157/13074368
|View full text |Cite
|
Sign up to set email alerts
|

Variables relacionadas con la satisfacción laboral: un estudio transversal a partir del modelo EFQM

Abstract: Almost half of the staff surveyed in our hospital were satisfied or highly satisfied with the organizational climate. Satisfaction was strongly associated with positive evaluation of organizational characteristics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
12

Year Published

2009
2009
2016
2016

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(22 citation statements)
references
References 9 publications
0
10
0
12
Order By: Relevance
“…Salgado et al 1996Robles, et al 2005;Chiang, Salazar and Núñez, 2007;Chiang, Salazar, Huerta and Núñez, 2008) leadership (Alves, 2000;Gonzalez Parra, 2008;Contreras, et al 2009) the culture of the organization (Méndez Hernández andVargas, 2013, González et al, 2008) with the quality of service and quality of life at work (Bernal, Pedraza and Sánchez, 2015;Casas, Repullo, Lorenzo and Cañas, 2002). Studies have reported that organizational climate is a variable that relates to other variables interacting in the context of the organization.…”
Section: Archives Of Business Research (Abr)mentioning
confidence: 99%
“…Salgado et al 1996Robles, et al 2005;Chiang, Salazar and Núñez, 2007;Chiang, Salazar, Huerta and Núñez, 2008) leadership (Alves, 2000;Gonzalez Parra, 2008;Contreras, et al 2009) the culture of the organization (Méndez Hernández andVargas, 2013, González et al, 2008) with the quality of service and quality of life at work (Bernal, Pedraza and Sánchez, 2015;Casas, Repullo, Lorenzo and Cañas, 2002). Studies have reported that organizational climate is a variable that relates to other variables interacting in the context of the organization.…”
Section: Archives Of Business Research (Abr)mentioning
confidence: 99%
“…Por lo tanto, los cimientos de un buen clima laboral se relacionan básicamente con el adecuado funcionamiento de la organización y, más específicamente, con indicadores tales como la conciliación del trabajo con la vida familiar, las prestaciones sociales en la empresa, la satisfacción en el puesto de trabajo y la calidad directiva o el liderazgo, entre otros (Cuadra-Peralta & Veloso-Besio, 2010). Así pues, queda suficientemente acreditado que el aná-lisis del clima organizacional es muy relevante para la determinación del grado de satisfacción en el trabajo y, a su vez, dicha satisfacción está fuertemente asociada a la valoración positiva de las características propias de la organización (Robles-García, Dierssen-Sotos, Martínez-Ochoa, Herrera-Carral, Díaz-Mendi, & Llorca-Díaz, 2005). Chiang, Martín, y Nuñez (2010) afirman que la satisfacción laboral es importante en el análisis del comportamiento organizacional porque para la mayoría de los trabajadores representa un fin en sí misma o un medio para conseguir la satisfacción personal.…”
Section: Fundamentos Teóricosunclassified
“…There are other questionnaires which have been used in several studies, but not with the same frequency, such as the Index of Work Satisfaction (IWS) (Jernigan, Beggs & Kohut, 2002; Other questionnaires found with a scarce use in the literature are the Jobsat survey (Westover, Westover & Westover, 2010); the Dubai Job Satisfaction Survey (Abdulla et al, 2011); the Work Motivation and Job Satisfaction Scale (WMJSS) (Saleem, Mahmood & Mahmood, 2010); the German Job Satisfaction Survey (GJSS) (Liu et al, 2004); the WES-10 (Workplace and Employee survey) (Rossberg, Eiring & Friis, 2004); the Work Environment Survey (WES) (Houston, Meyer & Paewi, 2006); the European Employee Index; the Occupational Stress Indicator 2 (OSI2) (Spector & Fox, 2003); and the "encuesta de satisfacción de las personas", created by "Servicio Vasco de Salud" (Osakidetza) (Robles-García, Dierssen-Sotos, Martínez-Ochoa, Herrera-Carral, Rosa Díaz-Mendi & Llorca-Díaz, 2005).…”
mentioning
confidence: 99%